The art of malaria education: an arts-based malaria education model, Pepease-Kwahu, Ghana - Ntim, Stephanie B.; Johnson, Katherine J. (International Journal Of Community Medicine And Public Health, 2019)
Background: Malaria is a major health concern in Ghana as well as other countries in West Africa, where it is estimated that more than 300 million people are at risk of malaria infection. While prior research has highlighted promising school-based interventions often facilitated through textbook information or teacher-based lectures to promote awareness about the disease, less is known as to how well such interventions are able to actively involve and engage students in learning about malaria in their schools. Methods: This research examines the role of the performing arts as a heuristic for student-centered teaching and learning about malaria. Using a convergent parallel mixed-methods study design, an arts-based malaria education model was deployed in a junior high school in Pepease-Kwahu, Ghana. Results: The proposed product included a peer-peer education model through which students (n=77) demonstrated their learning of malaria through their own creation and participation in poetry, song, dance, and drama performances. Pre- and post- paper-based surveys, coupled with focus groups with student participants (n=10) were used to examine the impact of this program. Conclusions: Research findings currently show that the arts-based malaria education program can be beneficial to students, by requiring them to use the performing arts to engage with information about malaria transmission, prevention, and treatment. Students correctly identified that the malarial parasite is transmitted by a mosquito bite, and they correctly identified symptoms of malaria, although students were reluctant to say that they will regularly use insecticide-treated bed nets as a preventive measure for malaria.